Influence of the phases of the menstrual cycle on the ability to produce strengt in futsal players - Nabo, Joana (2022)
This study was designed to evaluate and compare the total strength and resistance strength of the lower limbs of futsal players during the follicular and luteal phases of the menstrual cycle. In this investigation, 14 women, aged between 17 and 33 years old, were evaluated, and each one performed two evaluations of each test, corresponding to the phases of the menstrual cycle: test of global force evaluation with the manual dynamometer (Baseline Smedley Digital, model 12-0286) and lower limb muscle strength test at different angular velocities (60º and 180º/s) with the isokinetic dynamometer (Biodex, System 3). The mean values of the evaluated parameters were, in each phase of the menstrual cycle: dominant upper limb – follicular and luteal phases: 30.571 ± 5.198 vs 31.200 ± 4.917 kg; peak torque at isokinetic knee extension - follicular and luteal phases: 177.714 ± 32.573 vs 175.443 ± 27.272 N • m. Based on the results obtained, it was concluded that, between the menstrual cycle phases, there were no significant differences in the total muscle strength production and in the dominant lower limb of futsal players